Performance of BALB/c and C57BL/6 mice under an incremental repeated acquisition of behavioral chains procedure - Johnson, Jennifer M. (2010)
BALB/c (n = 8) and C57BL/6 (n = 11) male mice were trained under an incremental repeated acquisition (IRA) procedure using two distinct training procedures: forward and backward chaining. A new metric for assessing progress on the IRA procedure, progress quotient (PQ), quantified progress as the product of chain length and number of reinforcers earned during a session divided by the total number of reinforcers earned. BALB/c mice progressed further, had higher overall responding, earned more reinforcers, and acquired the response sequences faster than the C57BL/6 mice on both training procedures. There were only minimal effects of training procedure for either strain. The strain differences found between BALB/c and C57BL/6 mice confirm the importance of genetic background to behavior. C57BL/6 mice may be deficient in learning as compared with BALB/c mice but other contributing factors probably include overall responding, motivation, and more rapid satiation or habituation to sucrose reinforcement by the C57BL/6 mice. PQ is a sensitive and valid measure of progress for use in studies of mastery-based incremental repeated acquisition and BALB/c mice perform this challenging learning task better than do C57BL/6 mice.